Effect of rare earth addition on microstructure and mechanical properties of Al-Si alloys: An overview - Joy-Yii, S.; Kurniawan, Denni (2014)
This paper reviews the effect of rare earth addition on aluminium-silicon (Al-Si) alloys of hypoeutectic, eutectic, and hypereutectic types. The effects of rare earth on metallurgy, tensile strength, tensile fracture surface and wear behaviour of Al-Si alloys are highlighted and discussed in this paper. It was concluded that adding rare earth element to Al-Si alloys reduces the grain size of primary Si, increases the tensile strength and decreases the friction coefficient decreases. These indicate enhanced mechanical properties for rare earth modified Al-Si alloys are likely. © (2014) Trans Tech Publications, Switzerland.